2022
DOI: 10.1002/jsfa.12352
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of PPARα‐thermogenesis gut microbiota interactions in obese mice administrated with zingerone

Abstract: Background This study aimed to uncover the potential effects of zingerone (ZIN), one of the bioactive compounds in ginger, on the development of obesity as well as the mechanisms responsible for these effects in C57BL/6J mice fed with a high‐fat diet (HFD). Results Supplementation with 0.2% (wt/wt) zingerone for 16 weeks significantly reduced the final body weight, liver weight, and epididymal white adipose tissue (eWAT) weight without changing the food intake of the mice when compared with the HFD group. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 58 publications
(120 reference statements)
0
1
0
Order By: Relevance
“…From the relative abundance of gut microbial composition, it can be observed that maternal HALEs diet resulted in significant changes in the gut microbiota of offspring, characterized by an increased Firmicutes/Bacteroidetes ratio at the phylum level. Previous studies have shown that the relative proportion of Bacteroidetes was reduced in obese mice ( 38 ), and the changes in Firmicutes/Bacteroidetes ratios have been closely associated with metabolic disorders, such as obesity and diabetes ( 39 ). In this study, the maternal HALEs diet significantly increased the abundance of Dubosiella, and Dubosiella had significantly increased abundance in high fat diet feeding mice, suggesting its specific role in the obesity-related metabolic phenotype ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…From the relative abundance of gut microbial composition, it can be observed that maternal HALEs diet resulted in significant changes in the gut microbiota of offspring, characterized by an increased Firmicutes/Bacteroidetes ratio at the phylum level. Previous studies have shown that the relative proportion of Bacteroidetes was reduced in obese mice ( 38 ), and the changes in Firmicutes/Bacteroidetes ratios have been closely associated with metabolic disorders, such as obesity and diabetes ( 39 ). In this study, the maternal HALEs diet significantly increased the abundance of Dubosiella, and Dubosiella had significantly increased abundance in high fat diet feeding mice, suggesting its specific role in the obesity-related metabolic phenotype ( 40 ).…”
Section: Discussionmentioning
confidence: 99%